1999
DOI: 10.1103/physrevb.59.12268
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature electron-paramagnetic-resonance study of extrinsic and intrinsic defects inCuGaSe2

Abstract: The low-temperature electron-paramagnetic resonance ͑EPR͒ of the compound semiconductor CuGaSe 2 was investigated. Spectra of as-grown lumps and powders with a defined maximum grain size were measured in X band. The spectra of two transition-metal impurities, Ni ϩ and Fe 2ϩ , could be identified and their appropriate EPR parameters are presented. The position of the Fermi-level energy within the forbidden zone as indicated by the occurrence of nickel and iron with these oxidation states is discussed by analogy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The symmetry of this Cu 2 + center is rhombic and its spin-Hamiltonian parameters (g factors and hyperfine structure constants) were given. The observed hyperfine structure constants A x EA y and the small difference between the observed g x [E2.07 (1)] and g y [2.18 (2)] [10,11] suggest that the rhombic part of Cu 2 + center is very small. So the symmetry of Cu 2 + center can be regarded as approximately tetragonal [thus, g ?…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…The symmetry of this Cu 2 + center is rhombic and its spin-Hamiltonian parameters (g factors and hyperfine structure constants) were given. The observed hyperfine structure constants A x EA y and the small difference between the observed g x [E2.07 (1)] and g y [2.18 (2)] [10,11] suggest that the rhombic part of Cu 2 + center is very small. So the symmetry of Cu 2 + center can be regarded as approximately tetragonal [thus, g ?…”
Section: Introductionmentioning
confidence: 80%
“…and for Cu 2 + in CuGaSe 2 , g 99 4g ? [10,11]. Until now no theoretical studies have been made to explain this difference.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the ESR as a probe for the properties of CuGaSe 2 to solar cell applications is not widely used. The first ESR study in CuGaSe 2 was reported by Birkholz and co-workers [6]. They have observed a pronounced ageing effect when the semiconducting material is contamined with Ni þ and Fe þ 2 ions.…”
Section: Introductionmentioning
confidence: 96%